A GREEN ECTRACTION TECHNOLOGIES FOR COSMETIC-GRADE AVOCADO OIL FOR SUSTAINABLE COSMETIC APPLICATIONS: A REVIEW - desi, desi permata sari (Indonesian Journal of Cosmetics, 2025)
Avocado oil has gained increasing attention as a functional lipid ingredient in cosmetic formulations due to its superior emollient performance and high content of unsaturated fatty acids, phytosterols, and natural antioxidants. The shift toward sustainable manufacturing has stimulated the development of green extraction technologies capable of producing cosmetic-grade avocado oil while preserving its bioactive quality. This review critically examines recent advances in avocado oil extraction, comparing conventional methods such as cold pressing and solvent extraction with emerging technologies including supercritical and subcritical carbon dioxide extraction, ultrasound-assisted aqueous extraction, microwave-assisted extraction, and enzyme-assisted processes. The influence of extraction conditions on oil yield, free fatty acid content, oxidative stability, and retention of functional compounds is discussed based on peer-reviewed studies from the last decade. Attention is given to the suitability of each technique for cosmetic-grade applications, considering solvent safety, thermal degradation, energy efficiency, and alignment with green chemistry principles. Current findings indicate that assisted and CO₂-based extraction methods offer higher oil purity and improved preservation of bioactive components with lower environmental impact. However, challenges remain in process scalability, cost effectiveness, and the lack of standardized quality specifications for cosmetic-grade avocado oil. Future research directions are proposed to support industrial implementation of sustainable extraction strategies and to establish consistent quality benchmarks for green chemistry-based cosmetic formulations. This review provides a comprehensive reference for researchers and cosmetic manufacturers seeking to integrate green extraction technologies into sustainable product development.